Effect of Sustainability Report Disclosure and Company Size on Company Performance - Silvryza, Jihan; Kusumawardani, Niken (PT. Riset Press International, 2024)
The study examines how sustainability report disclosure and company size impact Return on Assets (ROA) among telecommunications, basic chemicals, and other sectors listed on the Indonesia Stock Exchange from 2018 to 2022. Utilizing data from 15 companies over five years, the findings indicate that company size has a significant positive influence on ROA, suggesting that larger firms tend to be more profitable. However, sustainability report disclosure alone does not significantly affect ROA. This lack of impact may be attributed to limited environmental awareness and weak enforcement of waste management regulations in Indonesia. The research employs quantitative analysis, including multiple linear regression, to analyze the data and test hypotheses. The results highlight the need for improved environmental consciousness and stricter regulatory enforcement to enhance the effectiveness of sustainability reporting. Methodologically, the study focuses on descriptive statistical analysis and classical assumption tests, such as normality, heteroscedasticity, multicollinearity, and autocorrelation tests, to ensure the robustness of the regression model. The recommendations emphasize increasing environmental awareness and regulatory enforcement to strengthen the positive impacts of sustainability initiatives. Future research should consider broader sustainability indices and alternative metrics for company size to gain deeper insights into how these factors influence corporate performance, thereby enhancing the understanding of sustainability's role in financial outcomes.